Central Odontogenic Fibroma of Simple Type - Prasanth Thankappan; Naga Sirisha V. Chundru; Rajesh Amudala; Prashanthi Yanadi; S. A. K. Uroof Rahamthullah; Meeramma Botu (Case Reports in Dentistry)
Central odontogenic fibroma (COF) is an extremely rare benign tumor that accounts for 0.1% of all odontogenic tumors. It is a lesion associated with the crown of an unerupted tooth resembling dentigerous cyst. In this report, a 10-year-old male patient is presented, who was diagnosed with central odontogenic fibroma of simple type from clinical, radiological, and histopathological findings.